Polylactic Acid/Bamboo Leaf Extract Electrospun Mats with Antioxidant Activity for Food Packaging Applications - Francesco Lopresti; Elisa Capuana; Graziella Serio; Carla Gentile; Luigi Botta (Antioxidants)
This study focuses on developing an active and biodegradable packaging using electrospinning, with polylactic acid (PLA) as the matrix and bamboo leaf extract (BLE) as the antioxidant compound. The research systematically evaluates the relationship among process parameters, material properties, and structure. The electrospun membranes were produced using different BLE contents (10 wt%, 20 wt%, 30 wt%, and 40 wt%) and characterized by their morphology, mechanical properties, wettability, and antioxidant activity. Scanning electron microscopy (SEM) revealed BLE’s influence on fiber morphology, with a slight increase in diameter in PLA/BLE at 10% and 20%, attributed to higher viscosity. Conversely, PLA/BLE 30% and 40% showed a mild reduction in fiber diameter likely due to polyphenols’ capacity to enhance PLA chain mobility. Mechanical tests indicated proportional reductions in modulus, maximum stress, and strain at break, upon increasing the BLE concentration, although these parameters are still suitable for packaging applications. The decrease in modulus is attributed to polyphenol capacity to increase PLA chain mobility, while increased fragility results from embedded particles acting as local defects. Wettability tests demonstrated increased hydrophilicity with higher BLE content. Total polyphenol content, estimated through FOLIN assay, increased proportionally with incorporated BLE, impacting antioxidant properties assessed via FRAP assay.